Konstruksi dan Evaluasi Psikometrik Skala Counterproductive Work Behavior - Ardi, Muhammad; Widyarini, Nilam (Journal of Research and Measurement in Psychology: JPPP, 2025)
This study aims to develop and examine the validity and reliability of a Counterproductive Work Behavior (CWB) instrument in the context of online motorcycle taxi drivers, encompassing two main dimensions: CWB directed at the organization (CWB-O) and CWB directed at individuals (CWB-I). Involving 1,416 participants from across Indonesia, the instrument was constructed based on the theory of Jex and Britt (2014) and tested using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The CFA results indicate that the two-factor model has a good fit (CFI = 0.948; TLI = 0.941; RMSEA = 0.067), with high reliability (ω = 0.956 for CWB-O and ω = 0.759 for CWB-I). One item was removed due to the absence of significant loading on any factor. The instrument has been proven valid and reliable, and can be used as a tool to detect potential counterproductive behaviors among online drivers.